Orbital-selective band hybridisation at the charge density wave transition in monolayer TiTe2 - Tommaso Antonelli; Warda Rahim; Matthew D. Watson; Akhil Rajan; Oliver J. Clark; Alisa Danilenko; Kaycee Underwood; Igor Marković; Edgar Abarca-Morales; Seán R. Kavanagh; P. Le Fèvre; F. Bertran; et al. (npj Quantum Materials, 2022)
Abstract Reducing the thickness of a material to its two-dimensional (2D) limit can have dramatic consequences for its collective electronic states, including magnetism, superconductivity, and charge and spin ordering. An extreme case is TiTe2, where a charge density wave (CDW) emerges in the single-layer, which is absent for the bulk compound, and whose origin is still poorly understood. Here, we investigate the electronic band structure evolution across this CDW transition using temperature-dependent angle-resolved photoemission spectroscopy. Our study reveals an orbital-selective band hybridisation between the backfolded conduction and valence bands occurring at the CDW phase transition, which in turn leads to a significant electronic energy gain, underpinning the CDW transition. For the bulk compound, we show how this energy gain is almost completely suppressed due to the three-dimensionality of the electronic band structure, including via a k z -dependent band inversion which switches the orbital character of the valence states. Our study thus sheds new light on how control of the electronic dimensionality can be used to trigger the emergence of new collective states in 2D materials.